Layanan Nyeri Akut Pascaoperasi: Organisasi dan Implementasi - Sudadi; Mahmud; Bahrun, Nugraha Septian (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2019)
Acute pain is pain of recent onset, limited duration and usually related to a pathological process, disease,or injury. The experience of acute pain is universal, but hospital inpatients frequently suffer severe pain asa result of surgery, trauma or medical illness. In the hospital, two thirds of patients experience pain duringtheir admission. Within the surgical population, where the noxious stimulus is well defined and systems are in place to manage acute pain, almost 60% of patients experience severe pain in the postoperative period with a marked negative impact on health-related quality of life.The presence of Acute Pain Service (APS) including regional anesthesia services, has increased the awareness of patients and medical professionals that proper pain management in perioperative period is important to enhance patient’s well-being. A dedicated team, which aspires for excellence and good clinical governance, and appropriate organizational structure, will definitely help in achieving a pain-free hospital stay, especially for the surgical patients.